Implementation and effect of intensified case finding on diagnosis of tuberculosis in a large urban HIV clinic in Uganda: a retrospective cohort study. - Hermans Sabine; Nasuuna Esther; van Leth Frank; Byhoff Elena; Schwarz Miriam; Hoepelman Andy; Lange Joep; Manabe Yukari C (BMC, 2012)
Abstract Background Increased detection of tuberculosis (TB) using intensified or active case finding (ICF) is one of the cornerstones of the Stop TB Strategy, and contrasts with passive case finding (PCF) which relies on self-reported symptoms. There is no clear guidance on implementation strategies. We implemented ICF in addition to ongoing PCF in our large urban HIV clinic in July 2010 using a twice-daily announcement screen method by a trained peer educator, asking waiting patients to self-refer to a trained peer supporter for screening of TB symptoms. We sought to determine the associated effect on TB case detection. Methods Suspects were investigated by sputum smear, chest X-ray and ultrasound, if indicated. Routinely collected clinical and laboratory data were merged with the ICF register and TB clinic data for patients attending the clinic in 2010. We compared the yield of TB cases (defined as the prevalence of newly diagnosed TB cases in the screened population), the type of TB diagnosed and the total cost per TB case identified (in United States Dollars [USD]) for the period before and after ICF implementation. Results Of the 20,456 patients who visited the clinic in 2010, 614 were identified as TB suspects, 220 pre-ICF and 394 post-ICF (229 via PCF and 165 via ICF). The proportion diagnosed with TB dropped from 66% to 48% (60% in suspects identified through PCF and 31% through ICF). During the post-ICF period, TB suspects identified through ICF compared to PCF identification were more likely to be female, older, on ART and to have been enrolled in HIV care for a longer duration. The yield of combined PCF and ICF screening was 1.4% pre-ICF and 1.7% post-ICF with a cost per TB case identified of 12.29 USD and 21.80 USD, respectively. Conclusions Implementation of ICF in a large HIV clinic yielded more TB suspects and cases, but substantially increased costs and was unable to capture the majority of TB suspects who were referred for diagnosis by clinicians through PCF. The overall yield of TB cases in a mature HIV clinic was low, although targeted screening of those recently enrolled in care may increase the yield.